Radiolytic formation of the carbon dioxide radical anion in acetonitrile revealed by transient IR spectroscopy. Issue 15 (5th April 2018) - Grills, David C.; Lymar, Sergei V.
Abstract : First IR detection of CO2 ˙ − in acetonitrile, produced by radiation-induced CO2 reduction and oxidation of formate. Abstract : The solvated electron in CH3 CN is scavenged by CO2 with a rate constant of 3.2 × 10 10 M −1 s −1 to produce the carbon dioxide radical anion (CO2 ˙ − ), a strong and versatile reductant. Using pulse radiolysis with time-resolved IR detection, this radical is unambiguously identified by its absorption band at 1650 cm −1 corresponding to the antisymmetric CO2 ˙ − stretch. This assignment is confirmed by 13 C isotopic labelling experiments and DFT calculations. In neat CH3 CN, CO2 ˙ − decays on a ∼10 μs time scale via recombination with solvent-derived radicals (R˙) and solvated protons. Upon addition of formate (HCO2 − ), the radiation yield of CO2 ˙ − is substantially increased due to H-atom abstraction by R˙ from HCO2 − (R˙ + HCO2 − → RH + CO2 ˙ − ), which occurs in two kinetically separated steps. The rapid step involves the stronger H-abstracting CN˙, CH3 ˙, and possibly, H˙ primary radicals, while the slower step is due to the less reactive, but more abundant radical, CH2 CN˙. The removal of solvent radicals by HCO2 − also results in over a hundredfold increase in the CO2 ˙ − lifetime. CO2 ˙ − scavenging experiments suggest that at 50 mM HCO2 −, about 60% of the solvent-derived radicals are engaged in CO2 ˙ − generation. Even under CO2 saturation, no formation of the radical adduct, (CO2 )2 ˙ −, could be detected on the microsecond time scale.